Pengaruh Sabut Kelapa sebagai Bahan Tambah Campuran AC-BC Menggunakan Batu Gunung Barani - Retor Rante Tondok; Alpius; Monika D.M Palinggi (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
One of the uses of Coconut Coir as a paved mixture, currently has been widely used a variety of added ingredients to mixtures. This study is intended to find out the characteristics of AC-BC mixtures that use coconut coir added ingredients and also to find out the AC-BC mixture. The method used is conventional Marshall immersion obtained ac-BC mixture with coconut coir content as a added material that is 0%, 1%, 2%, 3%, 4% with asphalt content of 5%. As for the characteristic influence on each mixed composition, if the level of Coconut Coir increases, then the stability value is obtained 1300.74-2354.10 and VFB 72.28-75.70 which is increasing, while for vim values 4.18-3.52, flow 3.50-2.33 and VMA 15.08-14.49 which decreases. From the test results it can be concluded that the AC-BC mixture using the added ingredients of Kelapa Cout has fulfilled the general specification of bina marga 2018.